The Role of Artificial Intelligence-Based Service Quality and Digital Customer Experience in Strengthening Customer Loyalty Through Brand Equity in E-Logistics Companies - Irwan Chairuddin; Juliater Simarmata; Olfebri Olfebri; Yulianti Keke; Primadi Candra Susanto; Mohamad Arif Hernawan (Dinasti Publisher, 2026)
This study aims to analyze the role of artificial intelligence (AI)-based service quality and digital customer experience in strengthening customer loyalty, both directly and indirectly through brand equity mediation in e-logistics companies in Indonesia. The research employs a descriptive qualitative approach using a Literature Review model based on 50 relevant scientific articles obtained from national SINTA-indexed journals and reputable international databases such as Scopus. The study synthesizes previous research findings to understand consumer behavior dynamics in the rapidly growing digital logistics industry. The findings indicate that service quality has a significant influence on brand equity and customer loyalty in e-logistics companies in Indonesia. Digital customer experience also positively affects both brand equity and customer loyalty. In addition, brand equity is proven to have a strong influence on customer loyalty, indicating that a positive brand image and customer trust contribute to long-term customer commitment. The study further reveals that brand equity mediates the relationship between service quality and customer loyalty, as well as between digital customer experience and customer loyalty. These findings highlight the importance of improving AI-based service quality, optimizing digital platforms, and strengthening brand equity strategies to maintain customer loyalty and competitiveness in Indonesia’s e-logistics industry.